Chilling injury susceptibility of early-season “Sai Nam Peung” tangerine fruit and alteration of α-farnesene and conjugated trienols during low temperature storage - Usawadee Chanasut (2018)
© 2018, Chiang Mai University. All rights reserved. Susceptibility to chilling injury (CI) of early-season and mid-season “Sai Nam Peung” tangerine fruits and the involvement of conjugated trienols (CTols), an oxidative stress product of α-farnesene, after storage at 3±1 °C (90 %RH) for 3 weeks and during 12-day shelf life were studied. Changes in malondialdehyde (MDA), the lipid peroxidative product, electrolyte leakage (EL), weight loss and fruit qualities were determined. Early-season fruit developed CI symptoms such as rind pitting, oleocellosis and brown stain or surface scald during cold storage. The CI index, %EL and %weight loss (%WL) continuously increased after the fruits were removed from storage. The concentrations of MDA, α-farnesene and CTols between the CI rind tissue of the early-season fruit and the mid-season fruit were significantly different (p<0.05) after storage. The susceptibility to CI of early-season tangerine fruit was more related to fruit maturity at harvest and loss of membrane integrity.